1981
DOI: 10.1063/1.92398
|View full text |Cite
|
Sign up to set email alerts
|

Realization of temperature-compensated GaAs surface acoustic wave delay lines

Abstract: Compensation for the first-order temperature coefficient of phase delay (TCD) of GaAs surface acoustic wave delay lines has been experimentally achieved using a two-layer Au/SiO2 film coating. The negative TCD of SiO2 provides temperature compensation, while the mass loading effect of the gold layer provides nonleaky Rayleigh wave propagation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

1985
1985
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 5 publications
1
2
0
Order By: Relevance
“…The TCDs of the other transversal filters were estimated using the same method. We also characterized (001) GaAs-based SAW filters with the [1-10] propagation direction and confirmed that their TCD, 52.8 ppm/deg, is in good agreement with a previously reported value 5) (not depicted). The dependence of TCDs on hk, where h and k are the GaN layer thickness and SAW wave number (k ¼ 2=), respectively, for both propagation directions is shown in Fig.…”
supporting
confidence: 90%
“…The TCDs of the other transversal filters were estimated using the same method. We also characterized (001) GaAs-based SAW filters with the [1-10] propagation direction and confirmed that their TCD, 52.8 ppm/deg, is in good agreement with a previously reported value 5) (not depicted). The dependence of TCDs on hk, where h and k are the GaN layer thickness and SAW wave number (k ¼ 2=), respectively, for both propagation directions is shown in Fig.…”
supporting
confidence: 90%
“…In this simple model, a relaxation time [25,26,28] of the 2D electron system is contained within the sheet conductivity such that…”
Section: Surface Acoustic Wave Technique As a Probe Of Crxx(co Q)mentioning
confidence: 99%
“…The TCF of SAW fabricated on AlN/GaN/sapphire with 2-mm-thick AlN was found to be À40:9 ppm/ C, whose absolute value is smaller than those of SAW fabricated on bulk LiNbO 3 and GaAs substrates. 12,[31][32][33] The reports about TCFs of SAW devices on AlN still vary for various cases. [34][35][36][37][38] It is known that there is a trade-off between piezoelectric coupling and TCF.…”
Section: Temperature Effect On Saw Characteristicsmentioning
confidence: 99%